Sāmudrikaśāstram : Hindīṭīkāsahitam ; ṭīkākāraḥ Abhaya Kātyāyana. - Kātyāyana, Abhaya (Caukhambā Surabhāratī granthamālā, 2008)
On Hindu art of sex and body-signs predictions; includes Hindi explanation.